Mapping the Intellectual Structure of Institutional Voids Research in Entrepreneurial Economics - Loso Judijanto; Munir Azhari; Humairoh Humairoh; Achmad Syahfrudin Zulkarnnaeni; Taswati Nova Wijayaningrum (Eastasouth Institute, 2026)
This study aims to map the intellectual structure and evolution of institutional voids research within the field of entrepreneurial economics using a bibliometric approach. Institutional voids, defined as the absence of market-supporting institutions, play a critical role in shaping entrepreneurial activities, particularly in emerging and developing economies. Despite the increasing volume of related studies, the literature remains fragmented and lacks a comprehensive synthesis. To address this gap, this study analyzes publications indexed in the Scopus database from 2000 to 2025, employing bibliometric techniques such as co-authorship analysis, citation analysis, and keyword co-occurrence using VOSviewer. The findings reveal that the research field is characterized by a fragmented collaboration structure, dominated by a limited number of influential scholars and institutions, with weak inter-cluster connections. Geographically, knowledge production is concentrated in developed countries such as the United States and the United Kingdom, while emerging economies are increasingly contributing but remain relatively peripheral. Thematic analysis shows that institutional voids serve as a central concept linked to key areas such as entrepreneurship, economic development, and institutional theory, with recent trends shifting toward sustainability, innovation, and inclusive development. This study contributes by providing a systematic and comprehensive overview of the intellectual landscape of institutional voids research, identifying major themes, influential works, and emerging research directions. The findings offer valuable insights for researchers, policymakers, and practitioners, particularly in understanding how institutional deficiencies influence entrepreneurial dynamics and how future research can be directed toward more integrated, interdisciplinary, and contextually relevant studies.